Excitation and evolution of coronal oscillations in self-consistent 3D radiative MHD simulations of the solar atmosphere - Kohutova, P.; Popovas, A. (Astronomy and astrophysics (Berlin), 2021)
Context. Solar coronal loops are commonly subject to oscillations. Observations of coronal oscillations are used to infer physical properties of the coronal plasma using coronal seismology. Aims. Excitation and evolution of oscillations in coronal loops is typically studied using highly idealised models of magnetic flux tubes. In order to improve our understanding of coronal oscillations, it is necessary to consider the effect of realistic magnetic field topology and evolution. Methods. We study excitation and evolution of coronal oscillations in three-dimensional (3D) self-consistent simulations of solar atmosphere spanning from the convection zone to the solar corona using the radiation-magnetohydrodynamic (MHD) code Bifrost. We use forward-modelled extreme-ultraviolet emission and 3D tracing of magnetic field to analyse the oscillatory behaviour of individual magnetic loops. We further analyse the evolution of individual plasma velocity components along the loops using wavelet power spectra to capture changes in the oscillation periods. Results. Various types of oscillations commonly observed in the corona are present in the simulation. We detect standing oscillations in both transverse and longitudinal velocity components, including higher-order oscillation harmonics. We also show that self-consistent simulations reproduce the existence of two distinct regimes of transverse coronal oscillations: rapidly decaying oscillations triggered by impulsive events and sustained small-scale oscillations showing no observable damping. No harmonic drivers are detected at the footpoints of oscillating loops. Conclusions. Coronal loop oscillations are abundant in self-consistent 3D MHD simulations of the solar atmosphere. The dynamic evolution and variability of individual magnetic loops suggest that we need to re-evaluate our models of monolithic and static coronal loops with constant lengths in favour of more realistic models.